2007
DOI: 10.1017/s0007114507803394
|View full text |Cite
|
Sign up to set email alerts
|

Association between zinc pool sizes and iron stores in premenopausal women without anaemia

Abstract: The simultaneous occurrence of Zn and Fe deficiencies in man has been known since the discovery of human Zn deficiency. However, it is not established that low Fe stores per se or Fe-deficiency anaemia infer low Zn status. Therefore our objective was to identify relationships between Zn and Fe status in premenopausal women without anaemia. We also examined the contribution of food frequencies and blood loss to Zn and Fe status. The subjects were thirty-three apparently healthy premenopausal women without anaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 56 publications
3
27
0
1
Order By: Relevance
“…The study showed a prevalence of serum zinc deficiency (,70 lg/dL, or ,10.7 lmol/L) of 12% overall, but with 19.4% among low-income, African American, preschool children compared with 4.8% in Hispanic children, which indicated that zinc deficiency is more widespread in lowincome, urban, African American children than expected and potentially should be monitored. Because serum zinc may be an insensitive indicator of zinc status relative to other kinetic zinc parameters, such as the various zinc pool compartments, the serum zinc cutoff was changed to 81 lg/dL (12.3 lmol/L) to evaluate the prevalence of zinc deficiency, which increased to 44% at this cutoff (22). Given the significant relation between serum zinc concentrations and hemoglobin (r = 0.26, P , 0.001), children who are diagnosed with anemia should possibly be evaluated for zinc deficiency, a concept that requires more comprehensive population-based studies (23,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed a prevalence of serum zinc deficiency (,70 lg/dL, or ,10.7 lmol/L) of 12% overall, but with 19.4% among low-income, African American, preschool children compared with 4.8% in Hispanic children, which indicated that zinc deficiency is more widespread in lowincome, urban, African American children than expected and potentially should be monitored. Because serum zinc may be an insensitive indicator of zinc status relative to other kinetic zinc parameters, such as the various zinc pool compartments, the serum zinc cutoff was changed to 81 lg/dL (12.3 lmol/L) to evaluate the prevalence of zinc deficiency, which increased to 44% at this cutoff (22). Given the significant relation between serum zinc concentrations and hemoglobin (r = 0.26, P , 0.001), children who are diagnosed with anemia should possibly be evaluated for zinc deficiency, a concept that requires more comprehensive population-based studies (23,33).…”
Section: Discussionmentioning
confidence: 99%
“…Although zinc deficiency is not usually recognized as a major problem in developed countries, it rivals iron deficiency as a major contributor to overall micronutrient deficiency in developing countries (20,21). Significant linear relations have been identified between the iron and zinc statuses of individuals (22). There have also been reports of an increased prevalence of zinc deficiency among 12-36-mo-old and 6-9-yold Hispanic children from low-income families in the United States (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Poor Zn nutriture has been a prevailing worldwide public health problem (Yokoi et al, 2007) since the discovery of human Zn deficiency (Prasad et al, 1963). Relationships between Zn nutriture and brain function in humans have been reported (Sandstead et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Çinko eksikliği gelişmiş ülkelerde sık rastlanan bir sorun olmasa da, gelişmekte olan ülkelerde demir eksikliği tüm mikronütrientler için eksikliğe yol açabilen bir faktör olarak karşımıza çıkmaktadır. Demir ve çinko seviyeleri arasında lineer bir ilişki gözlenmektedir [11][12][13] .…”
Section: Discussionunclassified